Association of the Renal Resistive Index with Microvascular Complications in type 2 Diabetic Subjects - Ozmen, N. D.; Mousa, U.; Aydin, Y.; Deren, T.; Unlu, E. B. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Chronic complications are the leading causes of morbidity and mortality in the diabetic population. The intrarenal resistive index (RI) has been reported to be increased in hypertensive subjects with microalbuminuria and limited data is present for diabetic subjects. 101 subjects with Type 2 Diabetes Mellitus were included in the study. We grouped the study population according to the urinary albumin excretion (UAE). Group 1: UAE<30 mg/day (n=36); Group 2: UAE 30–300 mg/day (n: 37); Group 3: UAE>300 mg/day (n: 28). We also grouped the study population according to the intrarenal RI value. Group I consisted of subjects with RI≥0.70 and group II<0.70. The mean intrarenal RI values of patients in group 3 were higher than those of group 1 and group 2 (0.72 vs. 0.69 p=0.048; 0.72 vs. 0.69; p=0.048 respectively). The duration of diabetes, hip circumference, and hs-CRP levels were statistically significantly higher in subjects with intrarenal RI≥0.70 compared to those with intrarenal RI<0.70 (p:<0.001, 0.048 and 0.0148 respectively). Presence of retinopathy and neuropathy was statistically significantly higher in subjects with intrarenal RI≥0.70 compared to those with intrarenal RI<0.70. RI may predict the development of microvascular complications in diabetic subjects.
Keywords: diabetes mellitus; albuminuria; retinopathy; neuropathy; resistive index